2011
DOI: 10.1111/j.1365-2052.2011.02278.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide associations for investigating time‐dependent genetic effects for milk production traits in dairy cattle

Abstract: Phenotypic variation in milk production traits has been described over the course of a lactation as well as between different parities. The objective of this study was to investigate whether variation in production is affected by different loci across lactations. A genome-wide association study (GWAS) using a 50-k SNP chip was conducted in 152 divergent German Holstein Friesian cows to test for association with milk production traits over different lactations. The first four lactations were analysed regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 38 publications
2
41
2
Order By: Relevance
“…The same analyses could be performed using just early or late lactation records. Lactation curve parameters have been used in similar modelling experiments and may further refine these numerous SNP associations [41]. …”
Section: Discussionmentioning
confidence: 99%
“…The same analyses could be performed using just early or late lactation records. Lactation curve parameters have been used in similar modelling experiments and may further refine these numerous SNP associations [41]. …”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have focused on time-dependent genetic associations in livestock to date and, as this study shows, the investigation of association at certain lactation stages seem to be a promising approach to detect loci with only small overall effects [13,46-48]. Thus, significant associations can sometimes only be found when the phenotype was recorded at the right time.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the known effects of the K232A locus in the DGAT1 ( diacylglycerol O-transferase 1 ) gene on milk yield and the protein production [9-11] are less pronounced or even reversed during the first 40 days of lactation [12]. Furthermore, it was shown that genetic loci significant for the main milk production traits change from early, peak to late lactation [13]. …”
Section: Introductionmentioning
confidence: 99%
“…In dairy cattle, for example, a common outcome is the detection of significant markers mainly located on the BTA14, in the region of the DGAT1 locus. The MDA method was able to indicate a larger number of significant markers in comparison with one of the most popular approaches used in GWAS study, the GenAbel R package (Strucken et al 2012;Minozzi et al 2013). The reliability of the MDA, based on the resampling procedure and on the use of the Chebyshev's inequality, together with the biological soundness of the detected genes, suggests that the obtained results should not be interpreted in terms of an increase of false positives, but as an evidence of the larger power of this method compared to more conservative approaches.…”
Section: Discussionmentioning
confidence: 99%